Allergic Rhinitis Improvement in Asthmatic Children After Using Acaricidal Bait: A Randomized, Double-Blind, Cross-Placebo Study - Chen, Ming; Wu, Yufen; Yuan, Shuhua; Tang, Mingyu; Zhang, Lei; Chen, Jiande; Li, Luanluan; Wu, Jinhong; Zhang, Jing; Yin, Yong (Frontiers in Pediatrics, 2021)
Objective: This study aimed to evaluate the eﬀects of using acaricidal bait on the concentration of house dust mite (HDM) allergens, allergic rhinitis (AR) and asthma symptoms in children sensitized to HDMs. Study design: Sixty-six children (3 to 12 years old) with AR and asthma sensitized to HDMs were randomly assigned to receive an acaricidal bait intervention for 8 weeks and a placebo intervention for 8 weeks. A 4-week washout period separated the two interventions. The visual analogue scale (VAS) score, rhinitis control assessment test (RCAT) score, rhinoconjunctivitis quality of life questionnaire (RQLQ) score, asthma control questionnaire-5 (ACQ-5) score and HDM allergens were monitored. Results: HDM allergens were significantly decreased after 8 weeks (△der p2+f2 2.282 (3.516) µg/g vs. 0.147 (0.25) µg/g, P < 0.05) in the acaricidal bait group compared to the placebo group. The VAS score of rhinitis symptoms, the RCAT score and the RQLQ score in the acaricidal bait group were also significantly improved (△VAS 7.5(16) vs. 3(18), P < 0.05; △RCAT -3(5) vs. 0(7), P < 0.05; △RQLQ 4.5(8) vs. 1(8), P < 0.05), but the ACQ-5 score did not improve (△ACQ-5 0.2(0.4) vs. 0(0.65), P > 0.05). A multivariate model adjusted for sex, age, acaricidal bait, and intranasal corticosteroids (INCs) revealed that the use of inhaled corticosteroids (ICS) (OR 0.309; 95% CI 0.116-0.82; P < 0.05) and good control of rhinitis (OR 0.082; 95% CI 0.027-0.242; P < 0.001) were independently associated with good asthma control. Conclusion: Acaricidal baits reduced HDM exposure and improved rhinitis symptoms. Good control of rhinitis and ICS contributed to asthma symptom control. This trial is registered at www.chictr.org.cn.